2013
DOI: 10.1017/s1474746413000067
|View full text |Cite
|
Sign up to set email alerts
|

The Fragility of Self-Respect: Emotional Labour of Workfare Volunteering

Abstract: This article contributes to our empirical understanding of self-respect in rising meritocracies by focusing on the experiences of unemployed, low-skilled people recruited as workfare volunteers in the Netherlands. As many theorists have argued, the longterm unemployed struggle to maintain self-esteem. We found that workfare projects that introduce them to voluntary work can help them regain self-respect through four types of emotional labour: feeling respected through their newfound status, enjoying a craft, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 31 publications
4
34
0
1
Order By: Relevance
“…Participants often talked (directly or indirectly) about perceived or anticipated negative social reactions regarding their SEP, or they used compensation strategies to cope with (real or anticipated) negative reactions and to maintain their self-respect. Similar results were found in recent studies by Kampen, Elshout and Tonkens [39, 50], who found that long-term unemployed Dutch people struggled with self-esteem and self-respect, and that they also felt inferior, looked down upon and ashamed.…”
Section: Discussionsupporting
confidence: 91%
“…Participants often talked (directly or indirectly) about perceived or anticipated negative social reactions regarding their SEP, or they used compensation strategies to cope with (real or anticipated) negative reactions and to maintain their self-respect. Similar results were found in recent studies by Kampen, Elshout and Tonkens [39, 50], who found that long-term unemployed Dutch people struggled with self-esteem and self-respect, and that they also felt inferior, looked down upon and ashamed.…”
Section: Discussionsupporting
confidence: 91%
“…Kampen (2014) has shown how the volunteer route, which is supposed to lead to paid employment, often ends in being stuck in an unpaid volunteering position with little prospect of paid employment. As a result, workfare volunteers turn away from the labor market and attach to their volunteer job (Kampen et al 2013). Another study found that welfare recipients themselves often do not believe volunteering constitutes 'real' work experience, and doubt it will lead to paid work (Sawer 2006).…”
Section: Outcomes Of Workfare Volunteeringmentioning
confidence: 99%
“…The main way to do this is by doing volunteer work. Volunteering would also make jobless people more 'employable' (Kampen, Elshout, & Tonkens, 2013).…”
Section: Introductionmentioning
confidence: 99%